Band Merchandise Design "Double Degree" As A Promotional Medium To Increase Brand Equity and Fan Reach - Rebeca Hosiana Gracia; Andika Agung Sutrisno (Warna Komunikasi, 2025)
This research aims to design merchandise as a promotion strategy for the Double Degree band using the Design Thinking approach of Tim Brown and David Kelley, which includes the empathize, define, ideate, prototype, and test stages. Merchandise is positioned not only as a selling product, but also as a promotional medium and identity symbol that strengthens the emotional connection between the band and the fans. Visual consistency through style guides is important to maintain uniformity of elements such as logos, colours, and mascots. The design process is focused on understanding the needs of the audience and creating relevant creative solutions so that the resulting designs are attractive, functional, and able to expand the band's market reach and exposure organically, as well as being an additional source of income for indie bands in Indonesia.